2021
DOI: 10.1002/cplu.202100102
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Halogen‐Bond Preferences in Molecules with Multiple Acceptor Sites

Abstract: The interplay between hydrogen bonds (HBs) and halogen bonds (XBs), has been addressed by co‐crystallizing two halogen bond donors, 1,4‐diiodotetrafluorbenzene(DITFB) and 1,3,5‐trifluoro‐2,4,6‐triiodobenzene(TITFB) with four series of targets; N‐(pyridin‐2‐yl)benzamide (Bz‐X), N‐(pyridin‐2‐yl)picolinamides (2Pyr‐X), N‐(pyridin‐2‐yl)nicotinamides (3Pyr‐X), N‐(pyridin‐2‐yl)isonicotinamides (4Pyr‐X); X=H/Cl/Br/I. The structural outcomes were compared with interactions in the targets themselves. 13 co‐crystals wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Overall, our results demonstrate the presence of NX 2 (X = Cl, Br, I) units, equivalent to the X 3 synthon reported for halogen (X) bonding. 61 (ii) GAKGAB, 62 (iii) HEZGAW, 63 (iv) OJIHIA, 64 (v) PESZOE, 65 (vi) TUNXIM, 66 (vii) UXARIX, 67 (viii) VIXXAE 68 and (ix) YANPIP. 69 Table 3 Interaction energies of the NI 2 unit in each centroid structure and its classification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, our results demonstrate the presence of NX 2 (X = Cl, Br, I) units, equivalent to the X 3 synthon reported for halogen (X) bonding. 61 (ii) GAKGAB, 62 (iii) HEZGAW, 63 (iv) OJIHIA, 64 (v) PESZOE, 65 (vi) TUNXIM, 66 (vii) UXARIX, 67 (viii) VIXXAE 68 and (ix) YANPIP. 69 Table 3 Interaction energies of the NI 2 unit in each centroid structure and its classification.…”
Section: Discussionmentioning
confidence: 99%
“…Fig.9Molecular graphs of the centroid structures with the NI 2 unit. The CSD codes are: (i) BUNGEY,61 (ii) GAKGAB,62 (iii) HEZGAW,63 (iv) OJIHIA,64 (v) PESZOE,65 (vi) TUNXIM,66 (vii) UXARIX,67 (viii) VIXXAE 68 and (ix) YANPIP 69. …”
mentioning
confidence: 99%
“…In addition to the theoretical studies, a number of experimental X-ray charge density studies on halogen bonding, chalcogen bonding, , carbon bonding, and pnicogen bonding , have by now established their n → σ* nature and that they are predominantly of electrostatic originas direct interaction of a charge-depleted region on the bond donor atom and charge concentrated region on the acceptor atom. Halogen bond (XB), where one of the bonding partners is halogen atom or ion [as a charge depletion site, i.e., δ+ or Lewis acid center], has now attained the status of “structure directing noncovalent interaction”, not only in the solid state but also in the solution and gaseous states. , Ever increasing reports on the role halogen bonds in crystal engineering, supramolecular assemblies, and biological systems indicate its capability as a structure driving force with interaction energies comparable to that of hydrogen bonds. In complex molecules with multifunctional groups, the halogen mediated interactions are often looked at as “surrogates” with intermolecular packing mainly guided by established noncovalent bonding such as strong hydrogen bonds . Hence, molecular systems without any strong hydrogen bond donor–acceptor pairs are considered to be the most suitable substrates to study the real effect of halogen bonding interactions .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, it has been shown that molecules comprising both N and O potential acceptor sites exhibit a definite preference for the formation of I···N halogen bonds in crystal structures. As a result, the instances when I···O and I···N halogen bonds coexist in a given crystal structure are relatively rare. It has been well documented that in hydrogen-bonded structures, the introduction of polytopic hydrogen-bond donors increases the probability of weaker acceptors being involved in hydrogen bonds (and vice versa ). Extending this approach to halogen-bonded materials, a halogen-bond donor molecule that comprises multiple donor sites (a di- or tritopic donor) is more likely to form both I···N and I···O halogen bonds with ambidentate acceptors.…”
Section: Introductionmentioning
confidence: 99%